Pengaruh Profitabilitas, Likuiditas dan Struktur Modal Terhadap Nilai Perusahaan - Andrian, Andrian; Idayanti, Irma; Hikmah, Yulia; Saputra, Andi; Pratama, Ananda Nickola; Dzakinah, Syadza Walni Dzakinah (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This research discusses the influence of profitability, liquidity, and capital structure on firm value. Through the systematic literature review (SLR) method, which analyzes 20 journals, this research poses three research questions regarding the influence of these three factors on the value of the company. The research results show that profitability has a significant impact on company value, liquidity, and capital structure also contribute positively to company value. The implication of these findings indicates that liquidity has not yet fully influenced the value of the company.